2018
DOI: 10.1080/14459795.2018.1466188
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes, beliefs and impulsivity in online gambling addiction

Abstract: Gambling research often refers to attitude and belief measurements to distinguish between problem and non-problem gamblers. Past studies also indicated that problem gamblers have a tendency to steeply discount rewards. We join both research streams and investigate the relationships between attitudes and beliefs on gambling addiction with the moderating effects of delay discounting using a novel methodological approach of double-hurdle model. We hereby differentiate the five subdimensions of the Gambling Attitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 95 publications
2
4
0
Order By: Relevance
“…Our study used delay discounting measure of impulsivity which is yet to receive robust attention in Sub-Saharan Africa. Similar result has been previously reported (Trivedi & Teichert, 2018;Amlung et al, 2017). Thus, our report supports the position that impulsivity boosts the incidence of problem gambling and other problematic behavior (Haw, 2017;Yan et al, 2016;Sharma et al, 2014).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our study used delay discounting measure of impulsivity which is yet to receive robust attention in Sub-Saharan Africa. Similar result has been previously reported (Trivedi & Teichert, 2018;Amlung et al, 2017). Thus, our report supports the position that impulsivity boosts the incidence of problem gambling and other problematic behavior (Haw, 2017;Yan et al, 2016;Sharma et al, 2014).…”
Section: Discussionsupporting
confidence: 92%
“…Thus, the association between entrapment and problem gambling was dependent on the gambler's level of impulsiveness (or otherwise) during Soccer gambling. This result is similar to past research (Trivedi & Teichert 2018) finding that impulsivity moderates the relationship between entrapment and gambling behaviour.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Additionally, Marmet et al (2019) demonstrated how gambling, online sex, smartphone use, gaming, and Internet use explain a relatively high variance in social anxiety disorder, major depression, ADHD, and borderline personality disorder, likely highlighting shared commonalities between these constructs. In terms of individual differences, higher levels of neuroticism and/or impulsivity have been linked to online gambling (Trivedi and Teichert, 2018), pornography viewing (Wéry et al, 2018), online shopping (Lee, 2018), and social networking use (Marengo et al, 2020). For an overview on neuroscientific findings in this area, please see the review studies by Becker and Montag (2019), Wegmann et al (2018), andKuss et al (2018).…”
mentioning
confidence: 99%